Findriver- Driven Relationship among Shariah Compliant Indian and Indonesian Indices – An Empirical Evidence using Granger Causality - Soni, Badal; Roy, Sarthak (Ushus Journal of Business Management, 2021)
This paper attempts to establish the driver-driven relationship, co-integration, and causality relation between the Shariah indices of India and Indonesia. For this reason, two Indian Shariah indices, Nifty 500 and S&P BSE 500 Shariah and two Indonesian Shariah indices IDX Shariah and Jakarta Islamic Index (JII) have been taken into consideration. A total of 1585 data points have been taken into account, and the period of the study is from May 2013 to October 2019 (approximately six years and six months). Empirical evidence of the study proves that there is reciprocity among the Shariah index of India, Nifty 500 Shariah, and S&P BSE 500 Shariah. There exists no relationship between IDX Shariah and Jakarta Islamic Index when compared with Nifty 500 Shariah, individually. IDX Shariah is a driver index, though it is 11 years younger than Jakarta Islamic Index and, which is the driven index.